Study of Different of Surface Characteristics Between Gram Negative and Positive Bacteria - Zwein, L.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The study included evaluation of cell surface charge and hydrophobicity of Escherichia coli, Klebsilla aerogenes, Proteus spp, Bacillus cereus, Staphylococcus epidermidis, Staphylococcus aureus(1) and Staphylococcus aureus(2) were determined by hydrocarbon adherence and hydrophobic interaction chromatography. The results showed that the negative charge of cell surface of gram negative bacteria was much higher than on gram positive once when these bacteria were grown on nutrient agar at 37 c for 18 h . E.coli was more negative charged than Klebsilla aerogenes and Proteus spp. The hydrophobicity of gram positive bacteria was much higher than of gram negative once, and S. epidermidis was more than S. aureus(1) B.cereus. and S.aureus (2) . The hydrophobic characteristics was quite different when these bacteria were grown on nutrient broth in comparison with nutrient ager. However the hydrophobic character was lower in non-capsulated and sporalated bacteria than the capsulated and sporalated at 48 h.